تحقيق سورة النازعات من مخطوط جوامع التبيان في تفسير القرآن معين الدين محمد بن عبد الرحمن الإيجي المتوفى سنة 906هـ (Journal of the College of Basic Education, 2026)
The study investigates a surah of the Holy Qur’an from one of the manuscript interpretations. This interpretation was initially classified by its author under the title Jami’ al-Bayan fi Tafsir al-Qur’an when he was forty years old, and at this stage the book was brief in its first form, but within thirty-three years of its writing The first version added many footnotes to the book, then the author refined, revised, trimmed and corrected the book until it came out in the form it has now. Then the author changed the name to Jami’ al-Tibyan fi Tafsir al-Qur’an.